Intra-aortic balloon pump can be used after acute type A aortic dissection repair - Akiko Tanaka; Yuki Ikeno; Harleen K. Sandhu; Charles C. Miller III; Hazim J. Safi; Anthony L. Estrera (Journal of Cardiothoracic Surgery)
Abstract Objectives We analyzed our data to evaluate the safety and feasibility of intraoperative extracorporeal membrane oxygenation and intra-aortic balloon pump use in acute type A aortic dissection repair. Methods Between December 1999-December 2020, we identified patients who received intraoperative extracorporeal membrane oxygenation and/or intra-aortic balloon pump support to wean off cardiopulmonary bypass were retrospectively reviewed. Results A total of 690 patients who underwent acute type A dissection repair. In all, 31 patients received intraoperative circulatory support (11 extracorporeal membrane oxygenation, 20 intra-aortic balloon pump) to wean off cardiopulmonary bypass. In all, 14 patients (45%) were female and the median age was 65 years (interquartile range 51–73). Prior to the acute type A dissection repair, 13 (42%) had coronary malperfusion, 7 (23%) had visceral malperfusion, 4 (13%) presented with acute coronary syndrome, and 8 (26%) received cardiopulmonary resuscitation. The median clamp time was 108 min (interquartile range 89–157) and circulatory arrest time was 25 min (interquartile range 19–31). Concomitant procedures included 11 coronary artery bypass grafting (35%), 4 root replacements (13%) and 1 total arch replacement (3%). Overall, in-hospital mortality was 67%: 10 of 11 (91%) patients with extracorporeal membrane oxygenation and 11 of 19 patients (55%) with intra-aortic balloon pump expired. There were no intra-aortic balloon pump-specific aortic complications (i.e. aortic rupture, extension of dissection). Conclusions Outcomes after extracorporeal membrane oxygenation support in acute type A dissection were discouraging. There may be a role for intra-aortic balloon pump following acute type A dissection repair to allow patients to recover from cardiogenic shock in the selected patients.